The Universal Audience: Ideological Construct or Counter-Ideological Tool? - Schwartzman, Roy (Current Progress in Arts and Social Studies Research Vol. 4, 2024)
This study seeks to connect Chaim Perelman’s new rhetoric with critical theory, specifically Jürgen Habermas’ ideal speech situation, to develop a more nuanced understanding of how argumentative strategies interact with power and ideology. Juxtaposing critical analysis of Perelman’s writings with Habermas’ ideal speech situation reveals that the universal audience, although conceived as a normative ideal for rational argumentation, is itself embedded in ideological contexts. The universal audience can function as a mechanism for legitimizing institutionalized power relationships and entitling individuals to exert authority. It also, however, possesses potential as a counter-ideological tool when synthesized with the ideal speech situation. This synthesis offers a more robust, although still nascent, framework for understanding the interplay between argumentation, ideology, and power.